2020
DOI: 10.1002/ejoc.202000674
|View full text |Cite
|
Sign up to set email alerts
|

Primary Vinyl Ethers as Acetylene Surrogate: A Flexible Tool for Deuterium‐Labeled Pyrazole Synthesis

Abstract: A novel synthetic path to 1,3‐disubstituted pyrazoles and their deuterated derivatives was developed. It is based on the reaction of vinyl ethers with hydrazonoyl chlorides in the presence of triethylamine. The reaction mechanism, clarified by the joint experimental and computational study, involves 1,3‐dipolar cycloaddition of the in situ generated nitrile imines to vinyl ethers and subsequent cleavage of alcohol from the formed alkoxypyrazoline. The results highlight the possibility of using vinyl ethers as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…Summarizing the results of the experiments including calcium carbide usage as a surrogate of acetylene, one can propose that the CaC 2 −H 2 O mixture should be replaced with a neutral analog to avoid 1,2,4,5‐tetrazine decomposition at elevated temperatures (most of the tetrazines decomposed in the presence of Ca(OH) 2 ). Recently, we demonstrated that benzyl vinyl ether can be used as an acetylene surrogate in 1,3‐dipolar cycloaddition reactions [20] . In this way, pyrazoles were obtained in up to quantitative yields in a one‐pot manner.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Summarizing the results of the experiments including calcium carbide usage as a surrogate of acetylene, one can propose that the CaC 2 −H 2 O mixture should be replaced with a neutral analog to avoid 1,2,4,5‐tetrazine decomposition at elevated temperatures (most of the tetrazines decomposed in the presence of Ca(OH) 2 ). Recently, we demonstrated that benzyl vinyl ether can be used as an acetylene surrogate in 1,3‐dipolar cycloaddition reactions [20] . In this way, pyrazoles were obtained in up to quantitative yields in a one‐pot manner.…”
Section: Resultsmentioning
confidence: 98%
“…The second way to perform water‐ and base‐sensitive reactions with acetylene is to replace it with vinyl ethers [20] . Vinyl ethers are readily available and relatively nontoxic compounds with well‐known physical characteristics that can be used as safe and easily dosed acetylene surrogates [20–21] . From a certain point of view, vinyl ethers can be described as simple and safe reagents compared to acetylene itself.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ledovskaya et al reported that the weak organic base trimethylamine (TEA) could promote the 1,3-dipolar cycloaddition of vinyl ethers and hydrazonoyl chlorides to produce 1,3-disubstituted pyrazoles with absolute regioselectivity [ 28 ] ( Scheme 23 ).…”
Section: The Synthesis Of Pyrazole Scaffold Moleculesmentioning
confidence: 99%